Introducing Robotic Operating System as a Project-Based Learning in an Undergraduate Research Project - Santos, Tatiana M. B.; Favoreto, Daniel G. S. B.; Carneiro, Mirella M. de O.; Pinto, Milena F.; Zachi, Alessandro R. L.; Gouvea, Josiel A.; Manhães, Aline; Almeida, Luciana F.; Silva, Gabryel R. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Simultaneous Localization and Mapping (SLAM) algorithms play a vital role in the field of robotics and autonomous systems. This algorithm enables the machines to navigate in unknown and dynamic environments without prior knowledge. In recent years, the integration of SLAM algorithms in various applications has increased significantly, making it an essential field of study. However, SLAM algorithms’ significance in students’ education is still relatively unexplored. Therefore, as an undergraduate research project, this work presents a comprehensive study of the Robotic Operating System (ROS) and SLAM algorithms application in students’ education. By integrating SLAM algorithms into students’ education, this project addresses the need to foster a more practical, experiential learning environment. As a result, this project aims to enhance comprehension of contemporary robotics and equip students to actively contribute meaningfully to the realm of robotics.